Honest and Independent Character and Its Relationship with Islamic Elementary School Education / Karakter Jujur dan Mandiri serta Hubungannya dengan Pendidikan Madrasah Ibtidaiyah - Lutfiyah, Ayu; Dahlan Rabbanie, Muhammad (Al-Mudarris: Journal Of Education, 2020)
The purpose of this research is to see the relationship between honest character and independent character with the education of Islamic Elementary School. This research approach is quantitative. The teacher became a population in the research conducted in Islamic Elementary School Al Hidayah and Madrasah Ibtidaiyah Al Wasilah with a total of 22 teachers. As a result of the study, the first honest character relationship with MI education has occurred positively, the results of the correlates are calculated by the Pearson correlation obtained the value of the correlation coefficient 0459. Coefficient of determination value at 0210, meaning 21.0% variable of honest character influenced by Islamic Elementary School education. The Regresinya line is Å¶ = 6.341 x 0.634 X1. Second, there is also an independent character relationship with MI education has occurred positively. The final result of the Pearson correlation count and obtained a correlation value coefficient of 0477. The value of determination 0227 equals 22.7% of self-variable character variables influenced by Islamic Elementary School education. The Regresinya line is Å¶ = 8,545 + 0, 761X2.Â